Liquid hydrocarbon storage tank fires : prevention and response : a collection of booklets describing hazards and how to manage them - Institution of Chemical Engineers (Great Britain); British Petroleum Company (Rugby : Institution of Chemical Engineers, 2008)
Includes bibliographical references (p. 47)